Gene therapy for age-related macular degeneration: a promising frontier in vision preservation - Kiavash Hushmandi; Hiu Yan Lam; Wendy Meihua Wong; Wency Tan; Seyed-Hashem Daryabari; Russel J. Reiter; Najma Farahani; Alan Prem Kumar (Cell Communication and Signaling)
Abstract Age-related macular degeneration (AMD) is a leading cause of central vision loss, progressively impairing the retina and affecting millions worldwide. By 2040, global cases of AMD are projected to reach 300 million, posing a significant public health challenge. While early AMD may only cause mild visual impairment, advanced stages, particularly neovascular (wet) and non-neovascular (dry) AMD, can lead to severe vision loss or legal blindness, substantially affecting daily life. The introduction of anti-angiogenic therapies has revolutionized wet AMD treatment, offering a high probability of preserving or improving vision. However, these therapies do not halt AMD progression, and no definitive treatments exist for dry AMD. The limitations of current therapies, such as frequent injections and treatment resistance, underscore the urgent need for novel strategies. Gene therapy, which has shown success in treating other hereditary retinal diseases, offers a promising long-term solution for AMD by targeting retinal cells to produce therapeutic proteins. This review explores the potential of gene therapy for AMD, examining recent clinical trials and future treatment directions. Graphical Abstract